Analysis of Legal Actions for Civil Claims of First Travel Fraud Victims Post Jurisdiction of the Supreme Court Number 3096k/Pid.Sus/2018 in Demanding Damages - Ni Nyoman Intan Pratiwi Rahmawati; Tunggul Anshari Setia Negara; Hendarto Hadisuryo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This article is entitled " Analysis of Legal Efforts in Civil Lawsuits for Victims of First Travel Fraud After the Supreme Court's Decision Number 3096K/ Pid.Sus /2018 in Demanding Compensation " with 2 (two) main issues, namely: (1) Is the act against the law, correct? to be used as the basis for a lawsuit by the plaintiffs in case Number 52/ Pdt.G /2019/ Pn. Dpk? (2) What was the judge's consideration in the decision Number 52/ Pdt.G /2019/ Pn. Dpk so that he stated that he rejected all civil claims submitted by the victims of the First Travel congregation. This research is a type of legal research with normative juridical research methods. In addition, this study uses an analytical research approach and a case approach. The results of this article research indicate that substance existence from Regional Regulation Number 2 of 2019 concerning Permits to Open State Land this violate draft authority for area. one of them is as mean in Regional Regulation Number 2 of 2019 concerning Permits to Open State Land where There are 3 authorized parties in publishing Permission that is Camat, Secretary district and mayor is violate provision in regulation technical namely Decree of the Head of BPN No. 2 of 2003 concerning Norms and Standards Mechanism Management Authority Government in the Field Land Implemented by the Government District /City that gift permission open land is authority Regent / Mayor. As a Permission, then government to do function control to activities carried out by the community to suit with provision Regulation Applicable legislation, one of which is is Opening Land. Conclusion from writer that The Central Government is the authorities _ in Give Permission Opening the Land of the State. This thing can see in substance of TAP MPR No. IX of 2001 which was later issue presidential decree Number 34 of 2003 concerning National Policy in the Field of Land Affairs, and Decree of the Head of BPN No. 2 of 2003 concerning Norms and Standards Mechanism Management Authority Government in the Field Land Implemented by the Government District / City. So, there is conflict of norm a Between the Presidential Decree and the Decree of the Head of BPN with Samarinda City Regional Regulation Number 2 of 2019 concerning Permits to Open State Land. Consequences is authority in IMTN should be returned to the Ministry of Home Affairs, however because there is a Ministry of ATR/BPN then in skeleton complete conflict of norm must be understood returned to the Minister of ATR/BPN because the Minister of ATR BPN has authority related with State land that is not lands rights , and not on forest areas based on Government Regulation of the Republic of Indonesia Number 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration .